2018
DOI: 10.3389/fendo.2018.00648
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Exposure and Bisphenol-A: Implications for Diabetes Development

Abstract: Bisphenol-A (BPA) is one of the most widespread endocrine disrupting chemicals (EDCs). It is used as the base compound in the production of polycarbonate and other plastics present in many consumer products. It is also used as a building block in epoxy can coating and the thermal paper of cash register receipts. Humans are consistently exposed to BPA and, in consequence, this compound has been detected in the majority of individuals examined. Over the last decade, an enlarging body of evidence has provided a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 110 publications
(133 reference statements)
0
15
0
Order By: Relevance
“…People are exposed to BPA via dietary ingestion, inhalation, and dermal contact in daily life [12]. However, prolonged or high exposure to BPA during the early life may result in more permanent adverse effects, and increase the risk of chronic diseases, such as metabolic and cardiovascular disease, in adult life [8,24]. Therefore, it is important to elucidate the possible causal association between BPA exposure and childhood obesity by conducting two systematic reviews with meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…People are exposed to BPA via dietary ingestion, inhalation, and dermal contact in daily life [12]. However, prolonged or high exposure to BPA during the early life may result in more permanent adverse effects, and increase the risk of chronic diseases, such as metabolic and cardiovascular disease, in adult life [8,24]. Therefore, it is important to elucidate the possible causal association between BPA exposure and childhood obesity by conducting two systematic reviews with meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite debates between food and drug administrations and researchers about the endocrine disrupting effects of BPA, this monomer has been implicated in a plethora of etiologies including diabetes, obesity, and hypothalamic neuroendocrine dysfunction. Early developmental periods are also ostensibly sensitive to the effects of BPA (127129).…”
Section: Industrial and Agricultural Chemicalsmentioning
confidence: 99%
“…Another analysis using liver samples revealed that prolonged exposure to BPA could elevate the mRNA expression of GLUT2, in addition to essential factors needed for biosynthesis of cholesterol and other lipids. Accordingly, increased levels of plasma TG and cholesterol were observed after administrating BPA during about one month and hypercholesterolemia persisted for more than 8 months after BPA treatment (Tudurí et al, 2018). Besides, the study done by ul Haq et al, 2020 concluded that chronic BPA exposure might and induce oxidative stress status which metabolism of carbohydrates and lipids.…”
Section: B-clinical Examinationmentioning
confidence: 97%